2017
DOI: 10.1177/0004563216682536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the systemic inflammatory response, as provoked by elective orthopaedic surgery, on HbA1c

Abstract: Background In acutely ill patients with new onset hyperglycaemia, plasma glucose cannot reliably distinguish between stress hyperglycaemia and undiagnosed diabetes mellitus. We, therefore, investigated the diagnostic reliability of glycated haemoglobin (HbA1c) in acute illness by prospectively evaluating the effect of the systemic inflammatory response, as provoked by elective orthopaedic surgery, on HbA. Methods HbA and serum C-reactive protein concentrations were compared before and two days after elective k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, a prospective study of 30 patients undergoing elective orthopaedic surgery demonstrated no significant change in HbA1c despite a clear systemic inflammatory response 84. Therefore, we suggest that patients in whom an elevated HbA1c is found during an acute inflammatory episode undergo further screening for diabetes.…”
Section: Erythrocyte Turnovermentioning
confidence: 77%
“…However, a prospective study of 30 patients undergoing elective orthopaedic surgery demonstrated no significant change in HbA1c despite a clear systemic inflammatory response 84. Therefore, we suggest that patients in whom an elevated HbA1c is found during an acute inflammatory episode undergo further screening for diabetes.…”
Section: Erythrocyte Turnovermentioning
confidence: 77%
“…1,2 Unlike HbA1c, the effects of nonglycemic variables on fructosamine are largely unknown. Acute illness has no effect on HbA1c, 3,4 but its effect on fructosamine has never been studied. We, therefore, investigated the effect of an acute phase response (APR), as provoked by elective orthopedic surgery, on fructosamine.…”
mentioning
confidence: 99%